A note on linear recursions - Saeree Wananiyakul; Janyarak Tongsomporn (Arab Journal of Basic and Applied Sciences, 2023)
AbstractWe consider linear recursions of length two and related gap recursions where the indices may not be consecutive integers. Given a linear recursion of length two, we prove the existence of an explicit linear recursion of length [Formula: see text] with arbitrary distance between indices. Conversely, it is shown under some mild assumption that a linear recursion of length [Formula: see text] can be reduced to one of length two.